The auxin phenylacetic acid induces NIN expression in the actinorhizal plant Datisca glomerata, whereas cytokinin acts antagonistically - Marco Guedes Salgado; Pooja Jha Maity; Daniel Lundin; Katharina Pawlowski (PLoS ONE, 2025)
All nitrogen-fixing root nodule symbioses of angiosperms–legume and actinorhizal symbioses–possess a common ancestor. Molecular processes for the induction of root nodules are modulated by phytohormones, as is the case of the first nodulation-related transcription factor NODULE INCEPTION (NIN), whose expression can be induced by exogenous cytokinin in legumes. The process of actinorhizal nodule organogenesis is less well understood. To study the changes exerted by phytohormones on the expression of the orthologs of CYCLOPS, NIN, and NF-YA1 in the actinorhizal host Datisca glomerata, an axenic hydroponic system was established and used to examine the transcriptional responses (RT-qPCR) in roots treated with the synthetic cytokinin 6-Benzylaminopurine (BAP), the natural auxin Phenylacetic acid (PAA), and the synthetic auxin 1-Naphthaleneacetic acid (NAA). The model legume Lotus japonicus was used as positive control. Molecular readouts for auxins and cytokinin were established: DgSAUR1 for PAA, DgGH3.1. for NAA, and DgARR9 for BAP. L. japonicus NIN was induced by BAP, PAA, and NAA in a dosage- and time-dependent manner. While expression of D. glomerata NIN2 could not be induced in roots, D. glomerata NIN1 was induced by PAA; this induction was abolished in the presence of exogenous BAP. Furthermore, the induction of DgNIN1 expression by PAA required ethylene and gibberellic acid. This study suggests that while cytokinin signaling is central for cortex-induced nodules of L. japonicus, it acts antagonistically to the induction of nodule primordia of D. glomerata by PAA in the root pericycle.